p62/SQSTM1-TRAF6/RIP1 complexes activate NF-κB-mediated PD-L1 expression and promote T-cell apoptosis in MKN45 gastric cancer cells - Li, Shiyang; Guo, Lingling; Yang, Xuan; Yang, Minwei; Li, Xiaoqian; Ye, Tao; Jiang, Min; Ma, Jian (Journal of Gastrointestinal Oncology; Vol 17, No 3 (June 29, 2026): Journal of Gastrointestinal Oncology, 2026)
Background: Autophagy has been implicated in the regulation of programmed death-ligand 1 (PD-L1) expression in gastric cancer (GC) through a p62/SQSTM1-nuclear factor-κB (NF-κB) pathway. However, the adaptor complexes linking p62 to NF-κB activation and the functional impact of this axis on T-cell apoptosis remain incompletely understood.Methods: Human GC MKN45 cells were treated with the autophagy inhibitor chloroquine (CQ) and the NF-κB inhibitor, respectively. Following transfection with p62/SQSTM1 knockdown plasmids, cells were treated with CQ. PD-L1 and pathway-related molecules were assessed by real-time quantitative polymerase chain reaction (RT-qPCR), Western blotting and immunofluorescence. Protein-protein interactions were examined by co-immunoprecipitation. A co-culture system of MKN45 cells and activated human T cells was established to evaluate T-cell proliferation with Cell Counting Kit-8 (CCK-8), apoptosis with cleaved caspase-3 and cytokine production (IFN-γ, IL-2 and TNF-α by ELISA).Results: CQ treatment in MKN45 cells resulted in autophagy blockade accompanied by p62/SQSTM1 accumulation, NF-κB activation and increased PD-L1 expression at both messenger ribonucleic acid (mRNA) and protein levels. Modulation of p62 expression confirmed that p62 was required for CQ-induced NF-κB activation and PD-L1 up-regulation. Co-immunoprecipitation experiments demonstrated that p62 formed complexes with TRAF6 and RIP1, and that these interactions were enhanced by p62 overexpression or CQ treatment but attenuated by p62 knockdown. Functionally, co-culture with CQ-treated or p62-overexpressing MKN45 cells suppressed T-cell proliferation, increased T-cell apoptosis and decreased IFN-γ, IL-2 and TNF-α secretion. These effects were partially reversed by p62 knockdown, NF-κB inhibition.Conclusions: This study improves our molecular understanding of the p62/SQSTM1-NF-κB-PD-L1 signalling pathway by implicating TRAF6 and RIP1 as adaptor proteins in MKN45 GC cells. It also provides evidence that activation of this pathway promotes T-cell apoptosis and cytokine suppression. These results suggest that p62/NF-κB/PD-L1 signalling could be targeted to enhance anti-tumour immunity in GC.